Rebalancing Wrongs: Towards a New Law of Remedies for Aotearoa New Zealand - Hughes, Alister (Victoria University of Wellington Law Review, 2022)
Tikanga Māori is a central pillar of Aotearoa New Zealand and the common law is developing to reflect that. A new era of law is emerging, informed by both tikanga Māori and settler law. While this is an important, positive step towards establishing an appropriate domestic jurisprudence of Aotearoa New Zealand, misguided integration, no matter how well intentioned, is harmful. The ongoing collision between tikanga Māori and settler law in a legal context must be navigated carefully. It gives rise to the need for specific examination of different areas of law to consider how the two systems might interact. This article examines the law surrounding remedies and considers whether and how remedial structures in tikanga Māori and settler law might be reconciled. It undertakes a broader structural analysis and a closer examination of the specific aims of each remedial framework. Overall, it argues that, with a shift in underpinning rationale to one informed by tikanga Māori, existing common law remedies may be applied in ways consistent with, and that give effect to, tikanga Māori. Despite tensions between the two frameworks, the flexibility within both tikanga Māori and the settler common law is sufficient to allow them to come together into a new law of remedies in Aotearoa New Zealand.